Analysis of initial rhythm, witnessed status and delay to treatment among survivors of out-of-hospital cardiac arrest in Sweden. Issue 22 (3rd October 2010) - Holmgren, C; Bergfeldt, L; Edvardsson, N; Karlsson, T; Lindqvist, J; Silfverstolpe, J; Svensson, L; Herlitz, J
Abstract : Background: The characteristics of patients who survive out-of-hospital cardiac arrest (OHCA) are incompletely known. The characteristics of survivors of OHCA during a period of 16 years in Sweden are described. Methods: All the patients included in the Swedish Cardiac Arrest Registry between 1992 and 2007 in whom cardiopulmonary resuscitation was attempted and who were alive after 1 month were included in the survey. Results: In all, 2432 survivors were registered. Information on initial rhythm at their first ECG recording was missing in 11%. Of the remaining 2165 survivors, 80% had a shockable rhythm and 20% had a non-shockable rhythm. Only a minority with a shockable rhythm among the bystander-witnessed cases were defibrillated within 5 min after cardiac arrest. This proportion did not change during the entry period. Among survivors found in a non-shockable rhythm, the majority were bystander-witnessed cases and a few had a delay from cardiac arrest to ambulance arrival of <5 min. Of all survivors, more women (27%) than men (18%) were found in a non-shockable rhythm (p<0.0001). During the 16 years in which the register was used for this study, the proportion of survivors found in a shockable rhythm did not change significantly. The cerebral performance categories score indicated better cerebral function among patients found in a shockable rhythm than in those found in a non-shockable rhythm. Conclusion: Among survivors of OHCA, a substantial proportion was found in a non-shockable rhythm and this occurred more frequently in women than in men. The proportion of survivors found in a shockable rhythm has not changed markedly over time. Survivors found in a shockable rhythm had a better cerebral performance than survivors found in a non-shockable rhythm. The proportion of survivors who were bystander-witnessed and found in a shockable rhythm and defibrillated early is still remarkably low.